This moose belongs to me - Jeffers, Oliver (New York, NY : Philomel Books, an imprint of Penguin Group (USA) Inc., 2012)
A young boy learns that moose do not always follow the rules of proper pet behavior.
Booklist starred
Pub Weekly
School Library Journal starred
Booklist starred, December 2012
Bulletin (Center for Children's books), January 2013
Choice, April 2013
Keywords: Moose as pets -- Juvenile fiction; Pets -- Juvenile fiction; Moose as pets -- Fiction; Pets -- Fiction; Moose -- Fiction; Pets -- Fiction; Picture books for children